Green ice - Browne, Gerald A. (New York : Delacorte Press, 1978)
Cynical, ne'er-do-well New Yorker John Wiley, seeking to get away from it all, meets up with a self-destructive young heiress and earns the disfavor of the South American syndicate which controls the black market in Colombian emeralds
Keywords: Mystery -- Crime